Arthrogryposis multiplex congenita in Aberdeen Angus cattle in Uruguay - Romero,Agustín (2020)
ABSTRACT: Arthrogryposis multiplex congenita is reported for the first time in the Aberdeen Angus (AA) breed in Uruguay. In a commercial herd of 30 purebred Aberdeen Angus cows, two calves with severe musculoskeletal malformations died at birth. The cows had been inseminated using semen imported from Argentina from one elite AA sire only. At necropsy, one calf showed severe muscular atrophy, arthrogryposis affecting all four limbs and the spine, kyphoscoliosis and torticollis. Histopathology showed muscular atrophy with marked fiber size variation and abundant fibroadipose fibers. The central nervous system only showed congestion and edema due to dystocia, whereas the peripheral nerves and the number of motor neurons in the spinal appeared normal. DNA analysis confirmed arthrogryposis multiplex congenita. It is concluded that disease in Aberdeen Angus cattle is due to failure in the neuromuscular junction.